Strategi Guru Tahfidz dalam Meningkatkan Kualitas Hafalan Tahfidzul Quran di SMP Islam Plus Al-Fatih - Muhammad Hafiz Artasyah Nst; Hadi Saputra Panggabean; Tumiran Tumiran (Medan Resource Center, 2026)
This study aims to analyze the strategies employed by tahfidz teachers to enhance the quality of students’ Qur’an memorization at SMP Islam Plus Al-Fatih. The research adopts a qualitative approach to explore, in depth, the teaching strategies, learning processes, and supporting factors that influence memorization quality. The findings reveal that the strategies implemented by tahfidz teachers are structured, varied, and oriented toward achieving comprehensive memorization quality, including accuracy of recitation, fluency, and retention. The instructional process involves the application of tajwid and tartil methods to ensure correct pronunciation, as well as consistent repetition (muroja’ah) to strengthen memory retention. In addition, teachers play a crucial role as both motivators and facilitators by fostering students’ intrinsic motivation, promoting character education, and utilizing digital Qur’an applications as learning media. These approaches contribute to increased student engagement, discipline, and consistency in memorization. Furthermore, periodic memorization assessments are conducted to monitor and improve students’ memorization quality. These assessments function not only as evaluative tools but also as feedback mechanisms that support continuous improvement. Overall, the study concludes that effective tahfidz learning is achieved through the integration of structured instructional strategies, motivational support, and continuous evaluation. This synergy serves as a key factor in enhancing the quality of students’ Qur’an memorization